Clinical implications of aspirin resistance. (September 2007) - Patel, Darshana; Moonis, Majaz
Aspirin (acetylsalicylic acid) is one of the main therapeutic medications used in the prevention of thromboembolic vascular events. Aspirin exhibits its antiplatelet action by irreversibly inhibiting platelet cyclooxygenase-1 enzyme, thus preventing the production of thromboxane A2 (TXA2 ). Aspirin resistance, as measured in vitro, is the inability of aspirin to reduce platelet activation and aggregation by failure to suppress the platelet production of TXA2 . Laboratory tests of platelet TXA2 production or platelet function dependent on TXA2 can detect aspirin resistance in vitro . The clinical implication of this laboratory definition has not yet been elucidated via prospective trials that have controlled for confounders, such as hypertension, diabetes and dyslipidemia. Large meta-analyses have found low-dose aspirin to be as effective as high-dose aspirin in preventing vascular events, making a dose-dependent improvement in laboratory response clinically irrelevant. Possible causes of aspirin resistance include poor compliance, inadequate dose, drug interactions, genetic polymorphisms of cyclooxygenase-1, increased platelet turnover and upregulation of nonplatelet pathways of thromboxane production. However, there is currently no standardized approach to the diagnosis and no proven effective treatment for aspirin resistance. Further research exploring the mechanisms of aspirin resistance is needed in order to better define aspirin resistance, as well as to develop a standardized laboratory test that is specific and reliable, and can correlate with the clinical risk of vascular events. The intent of this paper is to review the literature discussing possible mechanisms, diagnostic testing and clinical trials of aspirin resistance and to discuss its clinical relevance as it pertains to cerebrovascular and cardiovascular disease.